2014
DOI: 10.1002/marc.201400478
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Gel Formation from Structurally Controlled Poly(Electrolytes) Through Multiple “Head-to-Body” Electrostatic Interactions

Abstract: Tuning the chain-end functionality of a short-chain cationic homopolymer, owing to the nature of the initiator used in the atom transfer radical polymerization (ATRP) polymerization step, can be used to mediate the formation of a gel of this poly(electrolyte) in water. While a neutral end group gives a solution of low viscosity, a highly homogeneous gel is obtained with a phosphonate anionic moiety, as characterized by rheometry and diffusion nuclear magnetic resonance (NMR). This novel type of supramolecular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…For fluoride counterions as well as PIm + Cl -, the rheological profile is that of pure water which confirms the visual observation. However all other samples behave as shear-thinning yield stress fluids, confirming our previous results with PIm + Br - [24]. As shown in Figure 4, soluble samples are solid-like (G G ) at small strain and flow at large strains (G G ) with a steep decrease of the moduli.…”
Section: Rheological Measurementssupporting
confidence: 88%
See 3 more Smart Citations
“…For fluoride counterions as well as PIm + Cl -, the rheological profile is that of pure water which confirms the visual observation. However all other samples behave as shear-thinning yield stress fluids, confirming our previous results with PIm + Br - [24]. As shown in Figure 4, soluble samples are solid-like (G G ) at small strain and flow at large strains (G G ) with a steep decrease of the moduli.…”
Section: Rheological Measurementssupporting
confidence: 88%
“…We have previously demonstrated that, due to the opposite charges of the phosphonate head, head-to-body ionic bonds are possible [24]. On the one hand, if at least two foreign heads attach to the same body, we obtain an effective cross-link point.…”
Section: Processionary Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…This result could be expected with regard to the neutral nature of the polymer chain, which limits the interaction with anionic phosphate substituents; conversely, this suggests that substituting the pendant neutral group on the polymer side chain by cationic moieties could be a relevant strategy in order to enhance binding affinities of fluorescent probes for DNA. 91…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%